Comparative antimicrobial activities of the penem WY-49605 (SUN5555) against recent clinical isolates from five U.S. medical centers. - Sewell, D (1995)
The in vitro activity of WY-49605 (SUN5555) (WY) was compared with those of cefaclor, cefixime, and amoxicillin-clavulanic acid against 2,958 consecutive clinical isolates from five medical centers and 402 respiratory pathogens from 18 other facilities. Most members of the family Enterobacteriaceae were inhibited by WY (MIC at which 50% of the isolates are inhibited [MIC50], < or = 2.0 micrograms/ml). MIC90s of > or = 8.0 micrograms/ml were observed for Enterobacter cloacae, Serratia spp., and Proteus mirabilis. WY was the most active drug against methicillin-susceptible Staphylococcus aureus (MIC90, 0.12 microgram/ml) and other coagulase-negative staphylococci (MIC90, 4.0 micrograms/ml). The four drugs were not active against nonenteric gram-negative bacilli, methicillin-resistant Staphylococcus aureus, and Staphylococcus haemolyticus. At 2.0 micrograms/ml, WY inhibited 82% of Enterococcus faecalis strains and was equal to or superior to the other drugs against streptococci, Haemophilus influenzae, and Moraxella catarrhalis.